Correlation of glycosylated hemoglobin with microalbuminuria to predict renal damage in diabetic patients - Kriplani, Dipsha; Kriplani, Akshay; Gupta, Vivek; Samal, N.; Bhake, Arvind; Mahajan, Satish (International Journal of Research in Medical Sciences, 2017)
Background: Regular screening of levels of glycosylated hemoglobin and microalbuminuria, diabetic nephropathy can be prevented. The aim was to assess and compare the levels of glycosylated hemoglobin, microalbuminuria and serum creatinine in type 2 diabetic patients divided in groups of those on default antidiabetic treatment compared with those on regular antidiabetic treatment and to assess its correlation in type 2 of diabetic nephropathy. Methods:Two hundred diabetic patients above 40 years of age and 200 age matched control subjects with levels of glycosylated hemoglobin < 6.5% and on regular antiglycemic therapy were selected. Fasting plasma sugar was estimated by the glucose oxidase (GOD) - glucose peroxidase (POD). Glycosylated hemoglobin and microalbuminuria level was measured by the immunoturbidimetric method and serum creatinine estimation was done by the Jaffe’s kinetic method. p value was drawn using the student’s paired t-test. Results: There is a strong correlation between the increase in the levels of glycosylated hemoglobin with the corresponding rise in the levels of microalbuminuria and serum creatinine. Conclusion: Periodic surveillance of the levels of microalbuminuria should be carried out in the type 2 diabetic patients to prevent further damage by early detection of diabetic nephropathy.